Influence of Surface Forces on Membrane Separations - Anatoly N. Filippov; Huseyin Selcuk (Membranes, 2022)
This Special Issue of Membranes, entitled “Influence of Surface Forces on Membrane Separation”, is published in honour of Professor Victor Mikhailovich Starov, Doctor of Science in Chemistry, Fellow of the Royal Society of Chemistry [...]